2021
DOI: 10.3311/ppme.18246
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Processing Parameters and Calcium-stearate on the Ejection Process of Injection Molded Poly(Lactic Acid) Products

Abstract: We investigated the ejection/demolding of continuous production of injection molded Poly(Lactic Acid) tensile testing specimens and analyzed the effect of 1 wt% Calcium-Stearate additive as demolding agent (sliding or mold release agent) on this process. We demonstrated that the Poly(Lactic Acid) specimens could get stuck in the mold or even break during demolding during continuous injection molding in a certain type of mold, which has a low draft angle and varying cavity width along the flow path. The standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The best way to control the process is to use sensors in the mold [4,5]. In case of injection molding, melt temperature, mold temperature, injection rate, holding time, and holding pressure significantly affect the properties of injection molded parts [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The best way to control the process is to use sensors in the mold [4,5]. In case of injection molding, melt temperature, mold temperature, injection rate, holding time, and holding pressure significantly affect the properties of injection molded parts [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, plasticizers can improve its flexibility. [5][6][7][8][9][10][11][12][13][14] Unfortunately, PLA often does not have suitable properties to be used as a structural material, but with reinforcement and additives, its mechanical properties can be greatly improved and it can be made suitable for engineering applications. 15 One promising reinforcing material is basalt fiber.…”
Section: Introductionmentioning
confidence: 99%
“…PLA is a rigid material with an elongation at break of only 2%–5%. However, plasticizers can improve its flexibility 5–14 …”
Section: Introductionmentioning
confidence: 99%
“…Tábi and Poloskei 51 evaluated the effect of incorporating 1% by weight of calcium stearate in the PLA matrix, aiming to understand the impact during injection molding. The authors found that the molding process improved and prevented defects in the samples, suggesting that calcium stearate was effective as a demolding agent.…”
Section: Introductionmentioning
confidence: 99%